INVESTIGATION INTO THE PARENTS’ CHOICE OF LANGUAGE TO BE FIRST ACQUIRED BY CHILDREN IN ABAKALIKI URBAN NIGERIA - Nwigwe, Nwakaego; Obeka, Ngozi O. (EBSU Journal of Social Sciences and Humanities, 2024)
This study is an investigation into the parents’ choice of language to be first acquired by children in Abakaliki, Urban. The study, which is a descriptive survey research design purposively sampled one hundred parents (100) of different language backgrounds residing in Abakaliki Urban, the language they brought up their children to speak first and reasons behind their choice. Questionnaire, Oral interview and Observation were the instruments for data-gathering. Results showed that among children under 5 years of age 93 (93%) understands their parents indigenous language but 80 (80%) could speak it. In age group of 6 – 11 years 96 (96%) understand their parents’ L1, while only 81% could speak it. this showed that one-third (1/3) of the children have not acquired their parents L1. Parents who brought up their children to speak L1 did so mainly because they felt the children ought to know the language and culture of their people. Parents who chose to bring up their children to speak English said it was because the children needed English for school. Regretting the growing inability of some children to speak indigenous language and the attendant identity crisis, parents gave some of the following advice: Parents should speak their L1 to their children right from birth and make them respond in L1, expose the children to folktales, songs and games in L1, take children home to the village and grandparents periodically among others. These will ensure that the indigenous language will not go into extinction in the near future.